Processable and nanofibrous polyaniline:polystyrene-sulphonate (nano-PANI:PSS) for the fabrication of catalyst-free ammonium sensors and enzyme-coupled urea biosensors - Uzunçar, Sinan; Meng, Lingyin; Turner, Anthony P. F.; Mak, Wing Cheung (Elsevier, 2020)
Tailoring conducting polymers (CPs) such as polyaniline (PANI) to deliver the appropriate morphology, electrochemical properties and processability is essential for the development of effective polymer-based electrochemical sensors and biosensors. Composite PANI electrodes for the detection of ammonium (NH4+) have been previously reported, but have been limited by their reliance on the electrocatalytic reaction between NH4+ and a metal/nano-catalyst. We report an advanced processable and nanofibrous polyaniline:polystyrene-sulphonate (nano-PANI:PSS) as a functional ink for the fabrication of catalyst-free NH4+ sensors and enzyme-coupled urea biosensors. The PSS provides both a soft-template for nanofibre formation and a poly-anionic charge compensator, enabling the detection of NH4+ based on an intrinsic doping/de-doping mechanism. The nanostructured morphology, chemical characteristics and electrochemical properties of the nano-PANI:PSS were characterised. We fabricated 3D-hierarchical sensor interfaces composed of inter-connected nano-PANI:PSS fibres (diameter of ~50.3 ± 4.8 nm) for the detection of NH4+ with a wide linear range of 0.1–11.5 mM (R2 = 0.996) and high sensitivity of 106 mA M−1 cm−2. We further demonstrated the coupling of the enzyme urease with the nano-PANI:PSS to create a urea biosensor with an innovative biocatalytic product-to-dopant relay mechanism for the detection of urea, with a linear range of 0.2–0.9 mM (R2 = 0.971) and high sensitivity of 41 mA M−1 cm−2. Moreover, the nano-PANI:PSS-based sensors show good selectivity for the detection of NH4+and urea in a urine model containing common interfering molecules. This processable and fibrous nano-PANI:PSS provides new advance on CP-based transducer materials in the emerging field of printed organic sensors and biosensors.
Keywords: Nanofibre; Processable PANI:PSS; Doping/de-doping; Ammonium; Urea; Biosensors